Pension Fund Asset Allocation and Liability Discount Rates - Andonov, Aleksandar; Bauer, Rob M.M.J.; Cremers, K.J. Martijn (Review of Financial Studies, 2017)
The unique regulation of U.S. public pension funds links their liability discount rate to the expected return on assets, which gives them incentives to invest more in risky assets in order to report a better funding status. Comparing public and private pension funds in the United States, Canada, and Europe, we find that U.S. public pension funds act on their regulatory incentives. U.S. public pension funds with a higher level of underfunding per participant, as well as